2013
DOI: 10.1007/s12032-013-0542-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-22 is down-regulated in gastric cancer, and its overexpression inhibits cell migration and invasion via targeting transcription factor Sp1

Abstract: Accumulating evidence has shown that microRNAs are involved in multiple processes in cancer development and progression. Recently, miR-22 has been identified as a tumor-suppressing microRNA in many human cancers. However, the specific function of miR-22 in gastric cancer is unclear at this point. In this study, we first measured miR-22 expression level in 30 pairs of gastric cancer and matched normal tissues, two normal and six gastric cancer cell lines by real-time quantitative RT-PCR. We found that the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 29 publications
3
49
0
1
Order By: Relevance
“…miRs, which regulate the expression of their target genes by base pairing with seed sequences in the 3'-UTR of mRNAs, have been shown to regulate the expression of Sp1 (39,40). In a previous study, miR-22 was reported to be downregulated in GC and inhibited cell proliferation, migration and invasion by targeting Sp1 (41). The results of the present study suggested that miR-429 suppresses GC cell migration and invasion by directly targeting Sp1.…”
Section: Discussionsupporting
confidence: 57%
“…miRs, which regulate the expression of their target genes by base pairing with seed sequences in the 3'-UTR of mRNAs, have been shown to regulate the expression of Sp1 (39,40). In a previous study, miR-22 was reported to be downregulated in GC and inhibited cell proliferation, migration and invasion by targeting Sp1 (41). The results of the present study suggested that miR-429 suppresses GC cell migration and invasion by directly targeting Sp1.…”
Section: Discussionsupporting
confidence: 57%
“…miR-29b and miR-375 function as tumor suppressors in TSCC through targeting SP1 (39,40). miR-145, miR-133a, miR-133b, miR-22 and miR-335 serve an important role in the biology of gastric cancer by regulating SP1 directly (41)(42)(43). miR-145 was also found to regulate SP1 in ovarian cancer cells sensitized to paclitaxel (44).…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, ubiquitous miR-22 expression has been identified in a variety of tissues (14). We have identified that miR-22 is downregulated in gastric cancer and its overexpression inhibits cell migration and invasion (15). Lately, several targets of miR-22 have been reported to mediate its tumor-suppressive effect, such as tumor-suppressive PTEN, Max genes, p21 and oncogene c-Myc expression, etc (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%